Health service accreditation as a predictor of clinical and organisational performance: a blinded, random, stratified study. Issue 1 (19th February 2010) - Braithwaite, Jeffrey; Greenfield, David; Westbrook, Johanna; Pawsey, Marjorie; Westbrook, Mary; Gibberd, Robert; Naylor, Justine; Nathan, Sally; Robinson, Maureen; Runciman, Bill; Jackson, Margaret; Travaglia, Joanne; et al.
Abstract : Background: Despite the widespread use of accreditation in many countries, and prevailing beliefs that accreditation is associated with variables contributing to clinical care and organisational outcomes, little systematic research has been conducted to examine its validity as a predictor of healthcare performance. Objective: To determine whether accreditation performance is associated with self-reported clinical performance and independent ratings of four aspects of organisational performance. Design: Independent blinded assessment of these variables in a random, stratified sample of health service organisations. Settings: Acute care: large, medium and small health-service organisations in Australia. Study participants: Nineteen health service organisations employing 16 448 staff treating 321 289 inpatients and 1 971 087 non-inpatient services annually, representing approximately 5% of the Australian acute care health system. Main measures: Correlations of accreditation performance with organisational culture, organisational climate, consumer involvement, leadership and clinical performance. Results: Accreditation performance was significantly positively correlated with organisational culture (rho=0.618, p=0.005) and leadership (rho=0.616, p=0.005). There was a trend between accreditation and clinical performance (rho=0.450, p=0.080). Accreditation was unrelated to organisational climate (rho=0.378, p=0.110) and consumer involvement (rho=0.215, p=0.377). Conclusions: Accreditation results predict leadership behaviours and cultural characteristics of healthcare organisations but not organisational climate or consumer participation, and a positive trend between accreditation and clinical performance is noted.